First human case report of Crohn's disease with coexistent acute appendicitis treated by endoscopic retrograde appendicitis therapy - Cui, Guang-xing; Zulqarnain, Muhammad; Lou, Qi-feng; Shen, Hong-zhang; Lyu, Wen; Wang, Xia; Huang, Haitao; Mohamoud Abdi, Hamse; Gu, Lingfei; Fang, Shijie; Liu, Fangzhou; Ling, Liqian; et al. (Frontiers in Medicine, 2023)
BACKGROUND The coexistence of Crohn’s disease (CD) and acute appendicitis (AA) is rare. In this situation, therapeutic experience is lacking, and the strategy is paradoxical and intractable. Appendectomy is the gold standard for the treatment of AA whereas a nonsurgical approach is recommended for CD. CASE SUMMARY A 17-year-old boy was hospitalized for right lower abdominal pain with fever of 3 days. He had the CD for 8 years. Two years ago, he underwent surgery for anal fistula with the complication of CD. His temperature was elevated at 38.3C at admission. On physical examination, there was McBurney tenderness with mild rebound tenderness. Abdominal ultrasonography showed that the appendix was notably enlarged and dilated at 6.34 cm long and 2.76 cm wide. These findings were suggestive of uncomplicated AA in this patient with active CD. Endoscopic retrograde appendicitis therapy (ERAT) was performed. The patient had complete pain relief immediately after the procedure without tenderness in the right lower abdomen. During 18-month follow-up, he had no more attacks in his right lower abdomen. CONCLUSION ERAT was effective and safe in a CD patient with coexisting AA. Such cases can avoid surgery and its related complications.